Pengaruh Sistem Pengendalian Internal Pemerintah, Kompetensi Sumber Daya Manusia, Dan Standar Akuntansi Pemerintah Terhadap Kualitas Laporan Keuangan Di BPKAD Kota Denpasar - Ni Ketut Budi Ayu; I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2023)
A high-quality financial report is prepared to meet the qualitative characteristics of financial reporting that are relevant, reliable, comparable, and understandable. Financial reporting is a form of accountability and is essential to a company's survival as it reflects its performance through its financial condition. The objective of this study is to find out how applying government accounting standards, government internal control systems, and staff skills affects the quality of financial reporting for BPKAD Denpasar Municipality. All of the 125 people who work in the Denpasar City Region and Property and Financial Management Department were used in this study. The 61 people who took part in this study were chosen with the help of a targeted sampling method, and the results were tested with multiple linear regression analysis. This study's findings indicate that using government accounting standards, internal control mechanisms, and human resource skills positively impacts the quality of financial reporting by BPKAD Denpasar City. The results of this study indicate that Denpasar City BPKAD will be able to provide its employees with regular professional training related to preparing financial reports following government accounting standards, thereby improving their skills and competencies.